Reshaping Academic Libraries as Dynamic Partners and Knowledge Hubs for Research Productivity and Professional Development for Academics - Isiaka, Abdullahi Olayinka; Bamidele, Benjamin Adebisi; Ibitoye, Adelani Rotimi; Yusuf, Abdullahi Adebola (JINAV: Journal of Information and Visualization, 2025)
Academic libraries have long been regarded as repositories of knowledge, but their roles are rapidly evolving to meet the growing demands of research productivity and professional development among academics. This paper explores how libraries are transforming into dynamic partners and knowledge hubs to facilitate access to resources, tools, and services that enhance research output and academic growth among academics. This study adopted a survey design approach. The population of this study is all the 86 academic librarians from the nine university libraries in Kwara State. Total enumeration sampling technique was used and data were collected via questionnaire from the respondents. Data collected were analysed and presented with frequency counts, simple percentage and tables. Findings revealed that academic libraries play significance roles as dynamic partners in supporting research activities and professional development such as supporting multidisciplinary research; mentorship and consultation services; facilitating research collaboration among academics; engaging with global networks for shared resources; and training and capacity building for academics. Findings further revealed the invaluable roles of academic libraries as knowledge hubs in supporting research activities and professional development such as supporting scholarly publishing; enhanced access to research resources; promoting lifelong learning among academics; bibliometric analysis services; open-access initiative programs; and research data management and curation. Lastly, findings identified the innovative technologies academic libraries adopted to align their services with the changing needs of researchers and academics such as open-access academic databases; enhanced digital repositories; and cloud computing services. This study concluded that the roles of academic libraries as dynamic partners and knowledge hubs are paramount to research productivity and professional development of academics in Kwara State. This study recommended that academic libraries need to do more on building institutional partnerships by collaborating with academic departments, research centers, and external organizations to develop shared resources and programs that benefit researchers.